2013
DOI: 10.1007/s12032-012-0391-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of DNA alteration: loss of heterozygosity or allelic imbalance—promising for molecular staging of prostate cancers

Abstract: The biological behavior of prostate cancer is uncertain, and therefore, search for molecular prognostic markers associated with disease progression seems to be essential. We performed microsatellite allelotyping of DNA isolated from primary prostate tumors biopsies (prostate adenocarcinoma, PCa). We evaluated the frequency of allelic imbalance (AI), including loss of heterozygosity and/or microsatellite imbalance (LOH/MSI) as well as the association of these DNA alterations with clinicopathological variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In cases that were indistinguishable between MSI and loss of heterozygosity 54 , the allelic imbalance (AI) ratio was calculated. MSI was determined to be positive when the AI ratio (normal allele 1:normal allele 2/tumor allele 1:tumor allele 2) was <0.67 or >1.35, as previously reported 40 , 53 (Supplementary Fig. S2 ).…”
Section: Patients Materials and Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In cases that were indistinguishable between MSI and loss of heterozygosity 54 , the allelic imbalance (AI) ratio was calculated. MSI was determined to be positive when the AI ratio (normal allele 1:normal allele 2/tumor allele 1:tumor allele 2) was <0.67 or >1.35, as previously reported 40 , 53 (Supplementary Fig. S2 ).…”
Section: Patients Materials and Methodsmentioning
confidence: 92%
“…4.0 (Applied Biosystems). The MSI status was judged according to previous reports 40 , 53 , 54 (Supplementary Fig. S2 ).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…CMTM4 is tightly linked with CMTM1-3 on chromosome 16q22.1, a genomic region prone to both genetic and epigenetic modifications in various cancers. Chromosomal aberrations, such as deletions, amplifications [ 26 29 ], single nucleotide polymorphisms (SNPs) [ 30 ], loss of heterozygosity (LOH) and microsatellite instability (MSI) [ 31 , 32 ], as well as aberrant methylations [ 29 ], occur frequently in this region in different types of malignancies. Our previous studies have also shown that CMTM3 is frequently inactivated by promoter CpG methylation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported 22 , 25 , 43 , 49 , the following five microsatellite loci on chromosomes were examined for MSI based on the revised Bethesda panel 48 – 50 : BAT26, BAT25, D2S123, D5S346, and D17S250. MSI status was judged according to previous reports 43 , 49 , 51 , 52 (Supplementary Fig. S5 ).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%